The Effectiveness of Liquid Organic Fertilizer Made From Mixed Tofu Liquid Waste, Human Excreta Liquid Waste, Cow’s Urine and EM4 as a Media For Phytoplankton Culture - Fitriyani, Merry; Hasbi, M.; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Liquid wastes originated from tofu industries (T), human excreta (HE) liquid waste and cow’s urine (CU) are rich in organic materials and they are potential as basic ingredient for liquid fertilizer.To understand the N, P and K content in the liquid fertilizer made from mixed waste and its effectiveness in improving the growth of phytoplankton, a study has been conductedfrom September to October 2015.There were 7 treatments applied, namely P1 (100% T); P2 (90 % T and 10% CU) ; P3(90% T and 10% EM4); P4 (90% T and 10% HE); P5 (80% T, 10% CU and 10% EM4); P6 (80% T, 10% CU and 10% HE) and P7 (70% T, 10% CU, 10% HE and 10% EM4). Results shown that P6 is the best, with 22.590 mg/L Ncontent and 153 mg/L Pcontent. The K content in all treatments was almost the same. Addition of the liquid fertilizer into phytoplankton media significantly increases the abundance of phytoplankton. The highest abundance was obtained in P6. Based on data obtained, it can be concluded that the liquid fertilizer made from mixed tofu liquid wastes, human excreta, cow’s urine and EM4 is effective for increasing the phytoplankton abundance.Keyword: Tofu liquid waste, human excreta liquid waste, cow’s urine, EM4, Liquid Fertilizer, phytoplankton